A Primer to the Structure, Content and Linkage of the FDA's Manufacturer and User Facility Device Experience (MAUDE) Files. Issue 1 (14th June 2017) - Ensign, Lisa Garnsey; Cohen, K. Bretonnel
Introduction and Background: The US Food and Drug Administration (FDA)'s Manufacturer and User Facility Device Experience (MAUDE) database is a publicly available resource providing over 4 million records relating to medical device safety. Using downloadable MAUDE files avoids limitations of the online MAUDE search interface. However, naive file usage can result in errors, while independent discovery of the nuances required to correctly work with the database can be time-consuming. Practical information is provided to shorten this learning curve and obtain accurate results when using the MAUDE database files. MAUDE File Descriptions: The MAUDE database consists of 135 fields in four primary (Master Event, Device, Patient, Text) and two supplemental (Device Problems and Problem Code Descriptions) file types. When combined, these six files provide a detailed account of an adverse event or product problem report. Website instructions for joining the files are incomplete. Comprehensive details are provided to enable precise file linking. Lessons Learned: MAUDE files have irregularities that must be understood to download and work with the data efficiently. Accurate results depend upon combining the files correctly and understanding the difference between report and event denominators. Appreciating data availability can facilitate successful MAUDE investigations. Conclusion: The MAUDE database can provide key insights about medical device safety. Detailed information is provided about the structure, content and interrelationships of the MAUDE database files to enable investigators to use this valuable resource more quickly and accurately.